Effect of deep impurity levels on Schottky barrier diode characteristics - Korol, Anatoliy; Kitsai, M. Ye.; Strikha, V.; Sheka, D. (My University, 1975)
In the presence of an arbitrary number of deep donor levels volt-ampere and volt-farad characteristics are obtained for the Schottky barrier diode which contains a thin dielectric layer between the metal and the semiconductor.
Keywords: deep levels; Schottky barrier; бар’єр Шоткі; глибокі рівні; барьер Шоттки; глубокие уровни; кафедра фізики та професійної безпеки